Adverse events related to PBPC collection and mobilization for autologous transplantation in 10 years’ experience: procedures, efficiency, variables related to collection and safety profile - Pivkova Veljanovska, Aleksandra; Genadieva Stavrikj, Sonja; Stojanoski, Zlate; Chevrevska, Lidija; Krstevska Balkanov, Svetlana; Trajkova, Sanja; Panovska Stavridis, Irina; Georgievski, Borche (My University, 2011)
Objectives: We tried to evaluate the effi ciency, safety and risk factors of aphaeresis procedures used for autologous PBPC collections in a 10-year period in our transplant center. Thrombocytopenia, hypotension and citrate related adverse effects were evaluated as different biological variables. Material and methods: A total of 155 patients with hematological malignancies were analyzed (57 AML in fi rst remission, 33 HD, 37 MM, 20 NHL, 4ALL) that underwent mobilization of PBPC. The patients were mobilized either with CTX 3gr/m² + G-CSF 10mcg/kg starting or VP-16 (2gr/m²)+G-CSF 10mcg/ kg. Collections of PBSC were performed using Cobe spectra Baxter CS3000 aphaeresis system. Target of collection was >2, 0x10(6)/kg CD34+. The procedure was initiated when leukocyte count reached to 5x10(9)/L. Results: Both regimens were effective in the progenitor cell mobilization and almost 84% of analyzed patients reached at least 2x10(6)/kg CD34+ cells with median 3 (ranges 1-6) aphaeresis procedures. In 6% of patients adequate cell dose was not reachable and overall failure rate of mobilization of 17, 5%. Furthermore 15.6% failed to harvest the optimal 4x10(6)/ kgCD34+cells with >1 aphaeresis attempt. 48% patients in the CT/G-CSF group initiated aphaeresis on day 9, 34% on day 8 and 31% on day 10. Good mobilizers (GM) experienced at least one adverse event during aphaeresis compared with the no- GM. The percentage of absolute CD34+ before aphaeresis correlated with CD34+/cells/kg collected (R2=0, 62). The median of blood volume processed for body weight and the median time of aphaeresis was 7215ml (980ml-13450ml) in 202 min for GM and 8054ml (1450ml-14659ml) and 207min or no-GM. No correlation was found between CD34+/kg and volume processed. High correlation was found between the number of CD34+/kg and volume processed in the GM subject that reached the target of CD43+cells/kg only with one aphaeresis procedure (R2=0,87) We can conclude that the mobilizing regimens were adequate to achieve PBSC harvest in 84% of pts in our center that underwent autologous transplantation. The optimal approach to remobilization strategy remains unclear. Also we did not observe any signifi cant difference between GM and no-GM subjects in the adverse effect manifestation in reaching the CD34+cells/kg target, concerning the number of cells and volume processing. Maybe volume reducing of aphaeresis technique in future will shorten the time of achieving CD34+ target in GM subject.